International Monetary Fund Annual Report 1984. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1984)
This paper reviews the IMF's Annual Report for the fiscal year ended April 30, 1984. The report highlights that the performance of the world economy in 1983 and the early part of 1984 was significantly better than in the preceding several years. Economic expansion proceeded vigorously in the United States and Canada, and showed signs of spreading to other countries in the industrial world. Price inflation receded further in the seven largest industrial countries, dropping to its lowest level in 15 years. The current account deficit of developing countries was further reduced.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet